Impact of Proton Beam Irradiation on the Growth and Biochemical Indexes of Barley (Hordeum vulgare L.) Seedlings Grown under Salt Stress - Oprica, Lacramioara (Plants (Basel), 2020)
The present paper examines the effects of salt stress on the growth, pigments, lipid peroxidation and antioxidant ability of barley (Hordeum vulgare L.) seedlings raised from proton beam irradiated caryopses. In order to assess the effects of radiation on the early stages of plant growth and analyze its possible influence on the alleviation of salinity, 3 and 5 Gy doses were used on dried barley seeds and germination occurred in the presence/absence of NaCl (100 mM and 200 mM). After treatment, photosynthetic pigments increased in the 5 Gy variant, which registered a higher value than the control. Among the antioxidant enzymes studied (SOD, CAT, and POD) only CAT activity increased in proton beam irradiated seeds germinated under salinity conditions, which indicates the activation of antioxidant defense. The malondialdehyde (MDA) content declined with the increase of irradiation doses on seeds germinated at 200 mM NaCl. On the other hand, the concentration of 200 mM NaCl applied alone or combined with radiation revealed an increase in soluble protein content. The growth rate suggests that 3 Gy proton beam irradiation of barley seeds can alleviate the harmful effects of 100 mM NaCl salinity, given that seedlings’ growth rate increased by 1.95% compared to the control.